2015
DOI: 10.1177/1470320315595572
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the renal renin-angiotensin system in transgenic mice that express rat tonin

Abstract: Introduction: Tonin is an enzyme that is able to generate angiotensin II (Ang II) from angiotensin I (Ang I) or directly from angiotensinogen. Our goal was to characterize the renal renin-angiotensin system in transgenic mice that express rat tonin (TGM`(rTon)). Materials and methods: Mice were euthanized and the kidneys removed for analysis. Tonin activity was evaluated by radioimmunoassay and angiotensin I-converting enzyme (ACE) activity by HPLC. Tonin, ACE and angiotensin II-converting enzyme (ACE2) expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…ANG II and ANG-(1-7) values derived from these methods are typically far higher in plasma (26,33,51,135), kidney (33,110,114), vasculature (48), adipose tissue (33,115), and heart (42) than by RIA, HPLC-RIA, or HPLC-MS methods (Table 1). Indeed, two recent studies quantified mouse renal ANG-(1-7) at Ͼ1,000,000 fmol/g tissue (110) and rat plasma ANG II at Ͼ300,000 pM by HPLC analysis alone (33). Rubio-Ruiz et al (115) reported an ANG-(1-7) concentration of 6,000 pM in serum and Ͼ500,000 fmol/g in adipose tissue from male Wistar rats by capillary electrophoresis.…”
Section: Ras Peptidesmentioning
confidence: 99%
“…ANG II and ANG-(1-7) values derived from these methods are typically far higher in plasma (26,33,51,135), kidney (33,110,114), vasculature (48), adipose tissue (33,115), and heart (42) than by RIA, HPLC-RIA, or HPLC-MS methods (Table 1). Indeed, two recent studies quantified mouse renal ANG-(1-7) at Ͼ1,000,000 fmol/g tissue (110) and rat plasma ANG II at Ͼ300,000 pM by HPLC analysis alone (33). Rubio-Ruiz et al (115) reported an ANG-(1-7) concentration of 6,000 pM in serum and Ͼ500,000 fmol/g in adipose tissue from male Wistar rats by capillary electrophoresis.…”
Section: Ras Peptidesmentioning
confidence: 99%
“…Blockade of AT1R by losartan resulted in greater BP reduction in the TGM'(rTon) group than the in the WT group; this observation indicates that AT1R signaling was preponderant in the acute control of BP in TGM'(rTon) group. Taken together, increased Ang II due to increased circulating pathway of Ang I-tonin-AngII-AT1R is one of the mechanisms of a net result of higher BP in the TGM'(rTon) mice; however, we cannot be certain that the only route for higher Ang II formation in the circulation is via tonin in the TGM'(rTon) mouse, because tonin can affect the expression of other enzymes such as ACE as we have previously shown (17).…”
Section: Discussionmentioning
confidence: 86%
“…Transgenic TGM'(rTon) mice were generated by microinjection of the rat tonin transgene into zygotes as described by Ribeiro et al (17, 18). TGM'(rTon) mice exhibited higher tonin activity in the brain, heart, kidney, liver, and bladder compared to WT (17).…”
Section: Methodsmentioning
confidence: 99%